An in-situ polymerized solid polymer electrolyte enables excellent interfacial compatibility in lithium batteries. (10th March 2019) - Huang, Suqi; Cui, Zili; Qiao, Lixin; Xu, Gaojie; Zhang, Jianjun; Tang, Kun; Liu, Xiaochen; Wang, Qinglei; Zhou, Xinhong; Zhang, Botao; Cui, Guanglei
Abstract: Due to the ex-situ assembly technology of solid-state electrolyte, solid-state lithium batteries commonly show a poor electrolyte/electrode interfacial contact. Herein, we report an in-situ polymerized poly (tetrahydrofuran) (PTHF)-based solid polymer electrolyte (PTSPE) to resolve the poor interfacial contact problem in solid state lithium batteries. The in-situ formed PTSPE exhibits a high ionic conductivity (2.3 × 10 −4 S cm −1 ) and a wide electrochemical window (4.5 V) at 60 °C. More importantly, the in-situ formed PTSPE improves interfacial compatibility remarkably, suppressing the growth of lithium dendrites. It is revealed that boron trifluoride initiator works as functional additive to form LiF and B-O species at interface layer of lithium metal anode, alleviating lithium dendrites growth and undesired parasitic reactions. An as-assembled LiFePO4 /Li cell employing this in-situ formed PTSPE delivers a high discharge capacity of 142.3 mA h g −1 even after 100 cycles. The aforementioned results suggest that the in-situ polymerization technology of solid-state electrolyte is very promising for high-performance solid-state lithium batteries.